2006
DOI: 10.1002/pen.20508
|View full text |Cite
|
Sign up to set email alerts
|

Rheological behavior of starch–polycaprolactone (PCL) nanocomposite melts synthesized by reactive extrusion

Abstract: Rheological behavior of reactively extruded starch–PCL nanocomposite blends was evaluated in an off‐line capillary rheometer. Power law models for blends with different nanoclay volume fractions were developed using appropriate correction factors. Consistency coefficients K for blends containing starch were significantly higher than 100% PCL. Starch–PCL nanocomposite blends showed shear‐thinning behavior with higher pseudoplasticity than did 100% PCL. Viscosities of nanocomposite blends were significantly lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…The high values of n reported for PHB were comparable to those calculated for other biodegradable aliphatic polyesters [47,48]. Moreover, for all the samples, n decreased with the temperature.…”
Section: Processing Behavior: Rheological and Molecular Weight Measursupporting
confidence: 80%
“…The high values of n reported for PHB were comparable to those calculated for other biodegradable aliphatic polyesters [47,48]. Moreover, for all the samples, n decreased with the temperature.…”
Section: Processing Behavior: Rheological and Molecular Weight Measursupporting
confidence: 80%
“…5,7,8,13,15,16 To be processed starch has been plasticized with water, glycerol and other agents, the obtained material is widely known as thermoplastic starch (TPS). [2][3][4]7,8,[10][11][12][14][15][16][18][19][20]22 A recent review on starch-based polymers processing was presented by Liu et al 20 The techniques used to produce starch-based materials include compression molding, 3,5,9,13,19 injection molding, 4,7,8,14 extrusion, 3,4,7,8,10,[14][15][16] and film casting 1,17,19 and blowing. 2,7,8,[18][19][20]22 One of the most serious difficulties for production of starch-based ...…”
Section: Introductionmentioning
confidence: 98%
“…1,20 Since starch is immiscible with these polymers, a compatibilization may be required to obtain a useful product. 5,7,9,14,15 In addition, the mechanical properties of starch-based blends evolve with time through a series of complex processes like retrogradation and plasticization from environmental moisture. 1,9,13,16,22 There are reported some studies on TPS 1,18,19,22 and blends of TPS with other nonbiodegradable 2 and biodegradable polymers [6][7][8] films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the authors indicated that incorporation of sisal fibers might allow control biodegradation rate of PCL/TPS matrix in a more predictive manner. Kalambur and Rizvi [167][168][169] extensively investigated PCL/starch biocomposites fabricated by two steps performed in a single screw extrusion process, which is very promising from industrial application point of view. As demonstrated in Figure 21, the first step has been related to oxidation of starch by the replacement of hydroxyl groups by carboxyl or carbonyl groups and subsequently in second step, partially oxidized starch react with PCL.…”
Section: Composites Based On Biodegradable Polyestersmentioning
confidence: 99%